OAPEN Open Access Books Toolkit: A new resource for book authors - Emery, Christina (Septentrio Conference Series, 2020)
The OAPEN Open Access Books Toolkit is a brand new free resource for researchers, created through a collaborative writing process by global and diverse members of the academic community and scholarly communications organisations. The toolkit aims to help authors better understand open access (OA) for books, to increase trust in OA book publishing, to provide reliable and easy-to-find answers to questions from authors, and to provide guidance in the process of publishing an OA book. The toolkit was developed in a series of workshops for authors, hosted by the university libraries at Oxford, Glasgow and Utrecht, in collaboration with Springer Nature and OAPEN.The idea for this toolkit came about in a Researcher to Reader workshop where discussions concluded that a trusted single resource was needed to tackle the lack of awareness and understanding amongst authors about OA book publishing, and common misconceptions about licensing and quality which form important barriers in the transition to OA books.This poster describes the content and layout of the toolkit, and the journey in developing it. We want the academic community to get involved by spreading the word about this toolkit and providing feedback for further development. The OAPEN Foundation is a not-for-profit organisation that works with publishers to build a quality-controlled collection of open access books through the OAPEN Library and the Directory of Open Access Books, and provides services for publishers, libraries and research funders in the areas of deposit, quality assurance, dissemination, and digital preservation.
Keywords: Open access books; Open research; Toolkit; Resource; Researcher support